2010
DOI: 10.1073/pnas.1000041107
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of intracellular bacterial replication at the single cell level

Abstract: Several important pathogens cause disease by surviving and replicating within host cells. Bacterial proliferation is the product of both replication and killing undergone by the population. However, these processes are difficult to distinguish, and are usually assessed together by determination of net bacterial load. In addition, measurement of net load does not reveal heterogeneity within pathogen populations. This is particularly important in persistent infections in which slow or nongrowing bacteria are tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
314
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(354 citation statements)
references
References 31 publications
31
314
4
1
Order By: Relevance
“…Another study showed that persistent bacteria are sequestered within macrophages in systemic tissues, where they do not replicate and seem to be in a dormant-like state. This supports the idea of macrophages as a reservoir for persistent bacteria (Helaine et al, 2010). Another study published recently, showed that S. Typhimurium preferentially associates with anti-inflammatory/M2 macrophages at later stages of infection in mice (Eisele et al, 2013).…”
Section: Persistence In Immune Cellssupporting
confidence: 62%
“…Another study showed that persistent bacteria are sequestered within macrophages in systemic tissues, where they do not replicate and seem to be in a dormant-like state. This supports the idea of macrophages as a reservoir for persistent bacteria (Helaine et al, 2010). Another study published recently, showed that S. Typhimurium preferentially associates with anti-inflammatory/M2 macrophages at later stages of infection in mice (Eisele et al, 2013).…”
Section: Persistence In Immune Cellssupporting
confidence: 62%
“…Heterogeneity of intracellular bacterial population has already been reported for Salmonella. 35,51 Indeed, upon entry into macrophages, some Salmonella do not replicate and enter a dormant-like state. It is speculated that these living nonreplicating bacteria could represent a reservoir of persistent bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…THP-1 monocytes were differentiated into macrophages by treatment with 20 ng/ml phorbol myristate acetate (PMA) for 18 h. Primary bone marrow-derived macrophages (BMDMs) were obtained from wild-type and TLR-4 knockout BALB/c mice, extracted from tibia and femur, and grown as previously described. 35 …”
Section: Cell Culturementioning
confidence: 99%
“…From an ecological point of view, the quantitative study of nongrowing bacteria is highly relevant: ecosystems such as soil, sea water, and biofilms are dominated by nongrowing bacteria. Nongrowing bacteria have been recently linked to persistent infections, which represent a growing health issue (5-7), therefore an understanding of the physiology of these bacteria, both in vitro and in vivo (8) should have important clinical implications.…”
mentioning
confidence: 99%